Web Technologies
DOI: 10.4018/978-1-60566-982-3.ch071
|View full text |Cite
|
Sign up to set email alerts
|

Quality Enhancing the Continued Use of E-Government Web Sites

Abstract: This study empirically examines Web site quality toward the enhancement of the continued use of e-government Web sites by citizens. The web site quality under examination includes three main aspects, which are information quality, system quality, and service quality. The participants were 614 country-wide e-citizens of Thailand. The data were collected by means of a web-based survey and analyzed by using multiple regression analysis. The findings revealed that the three quality aspects enhanced the continued u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previousstudieshaveshownthatcomputerselfefficacyhasaneffectoncomputerrelatedtasks(Chun-Mei,Hsiao,Chien-Hua,&Su-Chang,2010;Paraskeva,Bouta,&Papagianni,2008;Simsek,2011).Computerself-efficacyisvitalininfluencing individuals feeling and behavior (Compeau & Higgins, 1995). Also, (Venkatesh & Davis, 1996) reportedthatcomputerself-efficacyisadeterminantofperceivedeaseofuse.Computerself-efficacy inrelationtoe-government,ithasbeendemonstratedthattheuseofe-governmentserviceswebsite wasinfluencedbycomputerself-efficacyofcitizens (Wangpipatwong,Chutimaskul,&Papasratorn, 2005).Thus,itisproposedthat:…”
Section: Computer Self-efficacymentioning
confidence: 99%
“…Previousstudieshaveshownthatcomputerselfefficacyhasaneffectoncomputerrelatedtasks(Chun-Mei,Hsiao,Chien-Hua,&Su-Chang,2010;Paraskeva,Bouta,&Papagianni,2008;Simsek,2011).Computerself-efficacyisvitalininfluencing individuals feeling and behavior (Compeau & Higgins, 1995). Also, (Venkatesh & Davis, 1996) reportedthatcomputerself-efficacyisadeterminantofperceivedeaseofuse.Computerself-efficacy inrelationtoe-government,ithasbeendemonstratedthattheuseofe-governmentserviceswebsite wasinfluencedbycomputerself-efficacyofcitizens (Wangpipatwong,Chutimaskul,&Papasratorn, 2005).Thus,itisproposedthat:…”
Section: Computer Self-efficacymentioning
confidence: 99%
“…government: Much research has been dedicated to the examination of information quality in egovernment and e-commerce. For instance, Wangpipatwong et al (2005) revealed information quality's significant impact on the e-government websites' adoption, David et al (2004) found it to be the strongest significant predictor of willingness to use e-government and Almahamid et al (2010) and it has a significant positive relation with intention to use e-government. Nevertheless, little or no research has been carried out on the impact of information quality upon the users' trust in egovernment adoption in the context of public sector organization.…”
Section: H1: Perceived Information Quality and Trust In E-mentioning
confidence: 99%